Selecting the Right Tool for the Task: A Hard-Soft Cake Eating Experiment with a Spoon and Fork - Bjarkum, Sondre; Chadoyan, Maximilian Stiegler; Medola, Fausto Orsi [UNESP]; Sandnes, Frode Eika (Springer Nature, 2021)
It is generally accepted that one need to select the correct tool for a given task. The same holds for eating utensils. A cake eating experiment was designed to determine if the visual appearance of cakes with different associated hardness would affect the choice of eating utensil. A total of 25 participants was recruited. The results did not reveal any effect of cake type, or presentation layout on the choice of eating utensil. It therefore seems that other factors, such as, for instance, customs and/or habits, are more influential in the choice of cake eating tool choice.
Keywords: Design; Eating utensil; Fork spoon; Hand dominance; Preference